Descriptive Analysis of Reasons of Participating Literacy Courses and Effects of Being Literate - Ayhan Erbay (Istanbul Kültür University, 2020)
The aim of this study is to find out the effects of literacy acquisition on adults' lives by exploring their background, experiences, and thoughts pertaining literacy's effect. In order to find effects of literacy, qualitative case study method was used and semi-structured interviews were carried with nine participants. It is found that almost all participants had similar life histories, which triggered them to looking for new solutions in order to cope with life. Age and psychological status of participants were especially powerful inputs in participation process. All participants became able to travel, read and write in order to perform in their daily lives without having relied on others after completion of the course. In addition, all participants in this study felt themselves more confident, improve their communication skills and develop sense of empowerment. As a result, it was found that the literacycoursesshould be separated according to the age and psychological status of the participants as well as content of the curriculum.